TREES COMMUNITIES IN SEASONALLY DRY MONTANE FOREST OF PICO DO JABRE, PARAIBA STATE - Cunha, Maria do Carmo Learth (2018)
This study was done on a Seasonal Semideciduous Montane Forest located at Pico do Jabre state Park (06°02’12’’ S and 34°45’12’’ W) between Maturéia and Mãe D’água (PB) municipalities, placed 360 kmfrom the sea and includes the highest regional elevation (1197 m).  It aims to investigate tree spatial distribution of populations and its association to local environmental factors to test the hypothesis that the spatial distribution of species along topographical gradient reflects different communities. To reach this target UPGMA, TWINSPAN and the indicator species analysis were complementarily applied, with significance of VI by Monte Carlotest. The results showed two floristic communities: PP including preserved plots and PAR colonizing disturbed and rocky plots. To highlight PP and PAR floristic differences a separated phytosociological analysis was run. Results showed distinct richness, diversity, density, low similarity and high beta diversity among communities. Byrsonima nitidifolia, and Maytenus distichophylla were found as PP indicator species and Eugenia ligustrina, Erythroxylum mucronatum and Myrciaria floribunda as PP preferential. There were no PAR indicator species. Miracrodruon urundeuva and Sapium glandulosum  stood out as PAR preferential species. The indicator species analysis showed five as preserved environment and three for disturbed/rocky environment indicators, as well as, floristic and structural differences along communities, formed according to human activities and rockyness.